Size and book-to-market anomalies and omitted leverage risk - Agarwal, Vineet; Poshakwale, Sunil S. (Taylor & Francis, 2010)
Ferguson and Shockley (2003. Equilibrium 'anomalies'.Journal of Finance 58: 2549-2580) develop a theoretical model and argue that size and book-to-market (B/M) effects in stock returns derive their cross-sectional explanatory power because they proxy for leverage and financial distress. Using UK data from 1979 to 2006, we provide evidence that the size factor of Fama and French (1993. Common risk factors in the returns on stocks and bonds.Journal of Financial Economics 33: 3-56) is indeed proxying for distress risk, while their distress factor is capturing leverage risk. However, anomalously low returns and higher exposure of small size and value stocks to the distress factor reduces the expected returns on these stocks and results in larger pricing errors. This leads to poor performance of the Ferguson and Shockley (2003. Equilibrium 'anomalies'.Journal of Finance 58: 2549-2580) model in the time series. Underperformance of distressed stocks casts doubt on the hypothesis that the explanatory power of size and B/M factors is due to the omitted debt claims in equity only proxy for market portfolio.